The use of the slope–area function to analyse process domains in complex badland landscapes. Issue 1 (20th September 2018) - Vergari, Francesca; Troiani, Francesco; Faulkner, Hazel; Del Monte, Maurizio; Della Seta, Marta; Ciccacci, Sirio; Fredi, Paola
Abstract: This paper explores the effectiveness of the widely‐used functional relationship between drainage area (A in m 2 ) and slope (S in m/m) to identify local process domains and aid interpretation of process interactions in a complex badland landscape. In order to perform this investigation, a series of sub‐basins tributary to the Formone River in the Orcia catchment (central Italy) were selected as a suitable study area within which to explore our questions, given these basins' general representativeness of local terrain, the availability of a high resolution digital terrain model and previous extensive geomorphological research. Eroding basins containing both calanchi and landslides are common in the sub‐humid badland landscape of central Italy, where field observation identifies a complex pattern of erosive processes associated with a history of uplift, despite which parts of the local landscape appear disconnected. Results reveal that the shape of all S–A curves (plotted using S data binned on log A) is comparable with that described in the literature, although sub‐basins containing calanchi generally plot with higher S values than non‐calanchi ones, except in the 'fluvial' section of the plots. Second, when viewed on total data (non‐binned) S–A plots, landslide source area domains and calanchi domains are entirely coincident in all basins, supporting a cause–effect relationship. Additional plotting of the frequency characteristics of the raw data in a new way supports the interpretation that calanchi frequently initiate in landslide scars. In general though, although the S–A plots can contribute to the disentanglement of geomorphological behaviour in some complex erosional landscapes, it became apparent that in this landscape, process domains do not separate out with clarity along the A axis as suggested by theory. Despite this, an alternative, broader‐scale morphoevolutive model can be proposed for the development of within‐landslide calanchi, driven by changes to basin connectivity to the base channel. © 2018 John Wiley & Sons, Ltd. Abstract : The effectiveness of the relationship between drainage area (A) and slope (S) to identify process domains and interactions in a complex badland landscape was explored. The shape of the S–A curves is comparable to that described in the literature, with basins containing calanchi showing some peculiarity, but in this landscape process domains do not separate out with clarity along the A axis, supporting a cause‐effect relationship between landslides and calanchi. A morphoevolutive model can be proposed, driven by changes to basin connectivity.